2021
DOI: 10.9758/cpn.2021.19.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Second-to-Fourth Digit Ratio (2D:4D) in Psychiatric Disorders: A Systematic Review of Case-control Studies

Abstract: The second-to-fourth digit ratio (2D:4D) is an indirect, retrospective, non-invasive measure that correlates negatively with intrauterine exposure to testosterone. The present meta-analysis aimed to evaluate if 2D:4D differs between patients with psychiatric disorders and controls. In September 2019, we searched in Web of Knowledge, PsycINFO, Embase, and CINHAL, and retrieved 619 papers. We finally included 43 case-control studies which compared the 2D:4D ratio of patients with autism spectrum disorder (ASD) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 95 publications
0
18
0
Order By: Relevance
“…8 Digit ratio has been found as a trait with sexual and ethnical variation 9 and suggested to be a putative biomarker by much recent evidence, since it has been found to correlate with various physiological, psychological, and pathological features. 10 It has been found that the lower right hand 2D:4D associate with lung cancer and…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 Digit ratio has been found as a trait with sexual and ethnical variation 9 and suggested to be a putative biomarker by much recent evidence, since it has been found to correlate with various physiological, psychological, and pathological features. 10 It has been found that the lower right hand 2D:4D associate with lung cancer and…”
mentioning
confidence: 99%
“…18 In order to declare the potential association between the prenatal testosterone and mood disorders, many studies have explored the link of the digit ratio with these diseases. 10 Our present study was planned to examine if the digit ratio, as a sign of antenatal testosterone exposure, associates with depression and hopelessness status in the Iranian women.…”
mentioning
confidence: 99%
“…Questionable is also how 2D:4D relates to autism spectrum disorders or psychiatric disorders in general. A recent meta‐analysis, which examined the 2D:4D ratio in patients with psychiatric disorders, found that overall, psychiatric patients had lower 2D:4D than healthy controls (Fusar‐Poli et al., 2020). In the ASD group particularly, the 2D:4D ratio was significantly lower than in healthy controls (Fusar‐Poli et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta‐analysis, which examined the 2D:4D ratio in patients with psychiatric disorders, found that overall, psychiatric patients had lower 2D:4D than healthy controls (Fusar‐Poli et al., 2020). In the ASD group particularly, the 2D:4D ratio was significantly lower than in healthy controls (Fusar‐Poli et al., 2020). However, the association of 2D:4D with autistic traits remains somewhat unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have suggested a link between the 2D:4D ratio and various diseases, including acne vulgaris 20,21 , seborrheic dermatitis 22 , psoriasis 23 , androgenetic alopecia 24 , thyroid disease 25 , lupus erythematosus 26 , multiple sclerosis 27 , ankylosing spondylitis 28 , some psychiatric disorders 29 , and some cancers (such as prostate and bladder) 30,31 . However, to our knowledge, there is not and published research on vitiligo and digit ratio.…”
mentioning
confidence: 99%